2012
DOI: 10.1089/jwh.2011.2886
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Behavioral Health of Women

Abstract: Smoking in women was associated with significantly higher rates of mental health and substance abuse problems. Substance abuse, being in a treatment setting, IPV, African American and mixed ethnicity, Medicaid insurance status, reduced income, and no home ownership were identified as predictors of smoking. Screening and evaluation of smoking status, mental health, substance use disorders, and the presence and impact of violence are essential for women's health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Using the five‐item Reexperiencing cluster from the PCL‐M, Bryan and Anestis () reported an alpha of .91 (95% CI [.71, 1.00]) for a small military sample, with a mean of 8.86 ( SD = 4.57). Jessup, Dibble, and Cooper () reported an alpha of .90 (95% CI [.84, .96]) for a sample of 1,021 women using a six‐item screener. Finally, Lang and Stein () summarized the diagnostic validity of two‐, three‐, four‐, and six‐item PCL‐SF versions, and none appears to be superior to the 17‐item version.…”
Section: Resultsmentioning
confidence: 99%
“…Using the five‐item Reexperiencing cluster from the PCL‐M, Bryan and Anestis () reported an alpha of .91 (95% CI [.71, 1.00]) for a small military sample, with a mean of 8.86 ( SD = 4.57). Jessup, Dibble, and Cooper () reported an alpha of .90 (95% CI [.84, .96]) for a sample of 1,021 women using a six‐item screener. Finally, Lang and Stein () summarized the diagnostic validity of two‐, three‐, four‐, and six‐item PCL‐SF versions, and none appears to be superior to the 17‐item version.…”
Section: Resultsmentioning
confidence: 99%
“…Additional factors include: emotional distress, depression, the belief that smoking is stress-relieving, concerns about weight control, lifetime intimate partner violence and childhood abuse (Jessup, Dibble, & Cooper, 2012;Kaufman & Augustson, 2008;Khor et al, 2006;McGee & Williams, 2006;World Health Organization [WHO], 2010). Parental smoking has also been linked to smoking among women (Oh et al, 2010), with adolescents with smoking parents more likely to become daily smokers (Peterson et al, 2006).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Some studies addressing adverse childhood experiences have further suggested that anxiety, especially in women, is a stronger predictor than depression of when someone classifies him or herself as a former smoker (Fuller-Thomson, Filippelli, & Lue-Crisostomo, 2013). It has also been suggested that the effect of adversity on smoking persistence is independent of either depression or anxiety (Taha et al, 2014) though with IPV other substance use (alcohol) severity and mental health, including PTSD-related symptoms, predict daily smoking (Jessup, Dibble, & Cooper, 2012; Sullivan et al, 2015). …”
Section: Introductionmentioning
confidence: 99%